HAK ATAS KEKAYAAN INTELEKTUAL SEBAGAI OBJEK JAMINAN FIDUSI (Lex Jurnalica, 2022)
This journal discusses intellectual property rights in this case copyright can be used as an object of fiduciary guarantee in accordance with article 16 paragraph (3) of Law No.28 of 2014 concerning Copyright. Although it can be the object of fiduciary guarantees, it does not necessarily make banks and other financial institutions easily provide their loans. The issues raised in this study are How the criteria for copyright to be used as a fiduciary guarantee and How to execute a fiduciary guarantee in the form of a copyright in the event of a default. To answer these problems, normative juridical legal research methods are used using a statutory approach using secondary data Data collection tools used through the study of documents or library materials, and the data analysis used is qualitative data analysis. In this study, it was found that the copyright criteria based on article 16 paragraph (3) of Law Number 28 of 2014 are movable objects that are not tangible. This is also juridically regulated in chapter 1 paragraph (2) Law Number 42 of 1999. As an intangible movable object, Copyright can used as fiduciary collateral. this is regulated in article 1 paragraph (2) of Law Number 42 of 1999, because here copyright is an intangible movable object and also copyright has economic value that can be used as an object of guarantee. Copyright that can be used as a fiduciary is a copyright that has been registered with the Directorate General of Intellectual Property. Copyright execution if used as a credit guarantee is through the Fiduciary Guarantee Act because the guarantee institutions that are banned by the Copyright Act of 2014 are fiduciaries because of the nature and control of the collateral objects, the fiduciary is the only debt guarantee institution that can be burdened with debt with the object of its guarantee in the form of Copyright